Context-concentric approach to the professional training of masters in intellectual property management - Bruyeva, V. (Problems of Engineer-Pedagogical Education, 2021)
The article reveals the essence of the problem of professional training of masters in intellectual property management in higher education institutions. The vision of domestic and foreign scientists on the use of innovative approaches and technologies in the training of managers for the field of intellectual property in higher education is analyzed. The main remarks of employers to universities that train managers for the field of intellectual property are highlighted. The list of requirements of the intellectual property market to the modern manager of the sphere of intellectual property is given. A context-concentric approach to the professional training of masters in intellectual property management as a tool of adaptive technology in higher education is proposed. The essence of the concepts of contextual approach, concentric approach and collaboration of these approaches in the professional training of masters of specialty 073 "Management" (specialization "Intellectual Property Management") is revealed. The definition of "Intellectualization of professional activity of the future head of intellectual property" is given. The presented arguments prove the expediency of introducing a context-concentric approach for the professional training of masters of intellectual property management. The list of skills which will be formed at masters of a specialty 073 "Management" (specialization "Management of intellectual property") at the context-concentric approach involved in educational process is given. The importance of interdisciplinary connections in the training of new types of managers for the field of intellectual property is considered in detail.